High strength parts and manufacturing method thereof

JP7631669B2Active Publication Date: 2025-02-19DAIDO STEEL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020056199
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-26
Publication Date
2025-02-19
Estimated Expiration
2040-03-26

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、静ねじり強度およびねじり疲労強度に優れた高強度部品及びその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631669000003
    Figure 0007631669000003
  • Figure 0007631669000004
    Figure 0007631669000004
  • Figure 0007631669000005
    Figure 0007631669000005
Patent Text Reader

Abstract

To provide a high strength component excellent in static torsional strength and torsional fatigue strength.SOLUTION: A high strength component consisting of steel having a predetermined component composition includes a carburizing and quenching layer on a surface layer part and has 0.80 μm or less of the arithmetic average roughness (Ra) of the surface, 1200-1650 MPa of a compressive residual stress and 490 HV or more of an equivalent hardness H defined by the following formula (1) on the basis of a hardness distribution from the surface to the inner center. H=Σ(Ki×Hi) / ΣKi .. the formula (1), where, Σ(Ki×Hi) is a value obtained by totaling the product of an area Ki (mm2) in a small region divided in the cross section of an object to be measured and a representative hardness Hi (HV) in the small region over the total small regions, and ΣKi is the area (mm2) of the total small regions.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high strength part and a method for manufacturing the same. [Background technology]

[0002] In order to ensure surface strength and internal toughness for parts such as gears and shafts used in automotive power transmission, surface treatments such as carburizing are applied to case-hardened steels such as JIS steels SCr420H and SCM420H. However, in order to meet the demands of higher output and lighter weight of vehicles, these parts are required to have even higher strength. For example, for shaft parts that are subjected to torsional torque, improvements in static torsional strength and torsional fatigue strength are required.

[0003] As a means for increasing the strength of parts, various proposals have been made regarding changes in the steel composition used and surface treatments applied to the surface of parts. For example, the following Patent Documents 1 to 3 disclose a method for increasing the compressive residual stress on the surface by processing into a part shape, performing carburizing and quenching, and then performing shot peening. However, these patent documents do not disclose examples of chemical compositions that satisfy the claims of the present invention. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-152330 A [Patent Document 2] JP 2014-210294 A [Patent Document 3] JP 2018-53337 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention is based on the above circumstances, and an object thereof is to provide a high-strength component having excellent static torsional strength and torsional fatigue strength and a method for manufacturing the same.

Means for Solving the Problems

[0006] As a result of intensive research focusing on the alloy composition of steel used for high-strength components, the present inventors have found that higher strength characteristics can be obtained by adjusting C-Si-Mn-Cu-Ni-Cr-Mo-Al-Ti-Nb-B-N. The present invention has been made based on such findings. By increasing the carbon content and adding boron to the standard carburizing steel, the static torsional characteristics are improved, and by improving the toughness by adding nickel, the torsional fatigue characteristics are improved. In addition, by reducing the silicon content and increasing the chromium content, the generation of carbides (over-carburizing) at the edge portion during vacuum carburizing is suppressed, and the torsional fatigue characteristics are improved.

[0007] In addition, after carburizing and quenching, it is also effective to perform shot peening on the surface of the component a plurality of times to impart a compressive residual stress to the surface of the component without deteriorating the surface roughness. This is because the generation and propagation of cracks when repeated stress is applied to the component can be suppressed, and the torsional fatigue strength can be improved.

[0008] Thus, the gist of the present invention is as follows

[0009] [1] A high-strength component made of steel containing, by mass%, 0.20 < C < 0.40, 0.50 < Si < 2.00, 0.20 < Mn < 2.00, P < 0.020, S < 0.020, 0 < Cu < 1.00, 0 < Ni < 2.00, 0.20 < Cr < 1.00, 0 < Mo < 1.00, 0.005 < Al < 0.100, 0.010 < Ti < 0.100, 0.010 < Nb < 0.100, 0.0005 < B < 0.0030, N < 0.005, with the balance being Fe and inevitable impurities, and having a carburized and quenched layer in the surface layer portion, wherein the arithmetic mean roughness (Ra) of the surface is 0.80 μm or less, the compressive residual stress is 1200 to 1650 MPa, and further, the equivalent hardness H defined by the following formula (1) is 490 HV or more based on the hardness distribution from the surface to the inner center. H = Σ(K i × H i ) / ΣK i ·· Equation (1) However, Σ(K i × H i ) is the sum of the products of the area K i (mm 2 ) of the small regions partitioned within the cross-section of the measurement target and the representative hardness H i (HV) of the small regions, and ΣK i is the total area (mm 2 ) of all the small regions.

[0010] [2] The high-strength component according to [1], further containing 0 < V < 0.50 in mass%.

[0011] [3] The high-strength component according to any one of [1] and [2], containing 0.26 < Ni < 2.00 in mass%.

[0012] [4] The high-strength component according to any one of [1] to [3], containing 0.30 < Mo < 1.00 in mass%.

[0013] [5] After processing the steel according to any one of [1] to [4] into the part shape, vacuum carburizing, quenching and tempering are performed, and then shot peening is performed using a projectile with a particle size of φ0.3 to 1.0 mm and a hardness of 700 HV or more, and then shot peening is further performed using a projectile with a particle size of φ0.05 to 0.2 mm and a hardness of 700 HV or more. A method for manufacturing a high-strength component, characterized by the above steps.

Advantages of the Invention

[0014] According to the present invention, it is possible to provide a high-strength component excellent in static torsional strength and torsional fatigue strength, and a method for manufacturing the same.

Brief Description of the Drawings

[0015] [Figure 1] It is a figure showing the shape of the test piece used for evaluation. [Diagram 2]It is an explanatory diagram for calculating equivalent hardness. [Diagram 3] It is a diagram showing the relationship between the proportional limit torque and the equivalent hardness of each example and comparative example.

Mode for Carrying Out the Invention

[0016] The high-strength part according to this embodiment contains C, Si, Mn, P, S, Cu, Ni, Cr, Mo, Al, Ti, Nb, B, and N, and the balance consists of Fe and inevitable impurities. Further, V may be contained. The reasons for limiting each chemical component in the high-strength part of this embodiment will be described in detail below. In the following description, unless otherwise specified, "%" means "mass%".

[0017] 0.20 < C < 0.40 C is an element effective for ensuring the internal (core) hardness. It is contained in an amount exceeding 0.20% to obtain the required hardness. However, excessive addition causes a decrease in toughness and corrosion resistance, so the upper limit is set to less than 0.40%. A preferred range of C is 0.21 < C < 0.35, and the internal hardness can be stably ensured.

[0018] 0.50 < Si < 2.00 Si is an element effective for suppressing the intrusion of C during vacuum carburizing and suppressing the formation of carbides due to excessive carburizing. It is contained in an amount exceeding 0.50% to obtain this effect. However, excessive addition causes a decrease in hot workability, so the upper limit is set to less than 2.00%. A preferred range of Si is 0.60 < Si < 1.50.

[0019] 0.20 < Mn < 2.00 Mn is an element effective for ensuring hardenability. It also forms MnS to render harmless the harm caused by S. However, excessive addition causes a decrease in workability and the formation of bainite, so the range is set to 0.20 < Mn < 2.00.

[0020] P < 0.020, S < 0.020 Since P and S are elements that are not favorable for the mechanical properties of the parts, their amounts are preferably small. Since P and S cause embrittlement due to grain boundary segregation, their upper limits are set to less than 0.020%.

[0021] 0 < Cu < 1.00 Cu is added because it has the effect of enhancing hardenability. However, excessive addition causes a decrease in hot forging properties, so the content is set to less than 1.00%.

[0022] 0 < Ni < 2.00 Ni is added for improving hardenability and also for improving toughness. However, excessive addition causes the formation of bainite, so its upper limit is set to less than 2.00%. The preferred range of Ni is 0.26 < Ni < 2.00.

[0023] 0.20 < Cr < 1.00 Cr is an element effective for ensuring internal hardness. However, excessive addition causes the formation of carbides due to excessive carburization and reduces fatigue strength, so its upper limit is set to less than 1.00%. The preferred range of Cr is 0.20 < Cr < 0.75.

[0024] 0 < Mo < 1.00 Mo is added for improving hardenability and also for improving toughness. However, excessive addition leads to deterioration of workability, so 0 < Mo < 1.00. The preferred range of Mo is 0.30 < Mo < 1.00.

[0025] 0.005 < Al < 0.100 Al is effective as a deoxidizing element and exhibits its effect when added in an amount exceeding 0.005%. However, excessive addition causes a decrease in strength due to Al2O3-based inclusions, so 0.005 < Al < 0.100.

[0026] 0.0005 < B < 0.0030 B is an element effective in improving hardenability. It segregates at grain boundaries, strengthens the grain boundaries, and has the effect of improving strength. However, excessive addition reacts with N in the steel to form BN, reducing toughness. Therefore, 0.0005 < B < 0.0030.

[0027] 0.010 < Ti < 0.100 When the above B forms BN, the original purpose of B addition cannot be achieved. However, B has a strong affinity for N and forms BN. Therefore, Ti, which has a stronger affinity for N than B, is used to form nitrides to fix N and ensure solid-solution B. However, excessive addition precipitates coarse nitrides, adversely affecting strength. Therefore, 0.010 < Ti < 0.100.

[0028] 0.010 < Nb < 0.100 Nb has the effect of forming carbides and suppressing abnormal grain growth during carburizing. However, excessive addition leads to a decrease in cold forging property. Therefore, 0.010 < Nb < 0.100.

[0029] N < 0.005 In the case of B-added steel, N forms BN, inhibiting the effect of B. Therefore, N < 0.005.

[0030] 0 < V < 0.50 V is an optional addition element, but a grain refinement effect and a tempering hardness improvement effect are expected. However, excessive addition leads to a decrease in workability and machinability. Therefore, it is preferably 0 < V < 0.50, and more preferably 0 < V < 0.30.

[0031] The high-strength component according to this embodiment has a carburized and hardened layer on the surface layer. The high-strength component of this embodiment is manufactured by processing steel having the above component composition into a component shape, performing vacuum carburizing, quenching and tempering, and further shot peening its surface.

[0032] The high-strength component of this embodiment has an arithmetic mean surface roughness (Ra) of 0.80 μm or less and a surface compressive residual stress of 1200 - 1650 MPa. The compressive residual stress imparted to the surface of the component has the effect of strengthening the stress concentration area that is the starting point of the initial crack and suppressing the occurrence of the initial crack, and is effective in improving the torsional fatigue properties. However, when compressive residual stress is imparted by shot peening, if the surface roughness of the component deteriorates, this will cause a decrease in fatigue strength, so in this example, the value of the average roughness (Ra) is also specified along with the compressive residual stress as described above. In this way, a high-strength component with the arithmetic mean roughness (Ra) and compressive residual stress of the surface specified can achieve the target torsional fatigue strength shown below. Note that the shot peening for imparting compressive residual stress may be performed only on a part of the high-strength component, that is, on the part where the torsional torque acts.

[0033] Furthermore, the high-strength part of this embodiment has an equivalent hardness H of 490HV or more, which is defined by the above formula (1) based on the hardness distribution from the part surface to the internal center. There is a correlation between the equivalent hardness H and the static torsional strength (proportional limit torque), and by setting the equivalent hardness H to 490HV or more, the target static torsional strength shown below can be achieved. A more preferable range of the equivalent hardness H is 495 to 600HV.

[0034] The shape of the high-strength part is not particularly limited as long as it is a shape appropriate for the type of part. For example, if the high-strength part is a shaft for power transmission, it may be a required shaft shape.

[0035] (Vacuum carburizing) In this embodiment, vacuum carburizing is used as the carburizing treatment. In vacuum carburizing, the atmosphere in the furnace is reduced in pressure (for example, 2 kPa or less), the furnace is heated and maintained at a temperature equal to or higher than the A3 point, and a hydrocarbon gas (for example, methane, propane, ethylene, acetylene, etc.) is directly introduced into the furnace as the carburizing gas. The gas comes into contact with the surface of the steel (the material to be treated), supplying carbon to the surface of the steel. The carbon then dissolves in the matrix, diffusing toward the inside. Vacuum carburizing does not cause oxidation of the material, so grain boundary oxidation is avoided, making it possible to increase fatigue strength. In addition, with vacuum carburizing, the carbon concentration is higher at the edges (corners) than at the flat parts, making it easier for carbides to form. This was one of the factors that reduced fatigue strength, but in this embodiment, the steel composition is made high Si and low Cr to suppress excessive carburization.

[0036] The carburizing pattern can be set as desired. After carburizing, the material may be directly quenched, or may be cooled and then reheated and quenched. Quenching is performed by placing the material in an oil bath at about 100 to 150°C. After quenching, tempering may be performed at, for example, about 120 to 180°C.

[0037] (Shot Peening) Shot peening has the effect of strengthening the stress concentration area that is the starting point of the initial crack and suppressing the occurrence of the initial crack, and is effective in improving the torsional fatigue properties. However, if the surface roughness of the part is increased by shot peening, it will become a factor of reducing the fatigue strength. In this example, shot peening is carried out in two stages to keep the arithmetic mean roughness (Ra) and compressive residual stress of the treated surface within the specified range.

[0038] In the first stage, shot peening is performed using shot material with a particle size of φ0.3-1.0 mm and a hardness of 700 HV or more under a shot air pressure of 0.2-0.6 MPa, because such conditions are suitable for imparting a compressive residual stress of 1200-1650 MPa to the surface of the treated material.

[0039] Next, in the second stage, shot peening is performed under a blast air pressure of 0.2-0.6MPa using shot material with a particle size of φ0.05-0.2mm and a hardness of 700HV or more. By using a fine particle shot material with a particle size of φ0.05-0.2mm, the deterioration of surface roughness can be eliminated. If a shot material with a particle size of more than φ1.0mm is used in the first stage, the surface roughness will deteriorate drastically, and even if fine particle shot peening is performed in the second stage, the surface roughness cannot be reduced, so the particle size of the shot material in the first stage must be φ1.0mm or less. EXAMPLES

[0040] Next, examples of the present invention will be described below. Test pieces (see FIG. 1) were prepared with the chemical compositions and shot peening conditions of the examples and comparative examples shown in Table 1 below, and various evaluations were performed. The chemical compositions or shot peening conditions of each of the comparative examples shown in Table 1 are outside the range of the present invention.

[0041] [Table 1]

[0042] 1. Preparation of Test Specimens A 150 kg steel ingot having the chemical composition shown in Table 1 above was melted in a vacuum induction melting furnace, and the resulting steel ingot was hot forged into a Φ40 mm round bar and normalized at 900°C to prepare a test material. Test pieces 10 having the shape shown in Figure 1 were then machined.

[0043] As shown in Fig. 1, the test piece 10 includes a shaft portion 12 and fixing portions 13 provided on both ends of the shaft portion 12, and a first through hole 14 is formed inside the shaft portion 12 and passing through the fixing portion 13. A second through hole 18 is formed in the axial center of the shaft portion 12, extending radially from the outer surface 16 and communicating with the first through hole 14. The dimensions of the test piece 10 in Fig. 1 are a length L1 of 100 mm, L2 of 60 mm, an outer diameter D1 of the shaft portion 12 of 22 mm, an outer diameter D2 of the fixing portion of 33 mm, an inner diameter D3 of the first through hole 14 of 7 mm, and an inner diameter D4 of the second through hole 18 of 4 mm.

[0044] 2. Vacuum carburizing treatment The test piece 10 machined into a predetermined shape was placed in a treatment furnace, and the treatment furnace was evacuated to a reduced pressure of 1500 Pa. The treatment temperature was changed from 850 to 1050°C, and carburization treatment was performed for 30 minutes to 4 hours. Next, quenching was performed in an oil bath at 100 to 150°C, and then tempering treatment was performed at 120 to 180°C for 120 minutes, resulting in a surface layer C concentration of 0.65 to 0.80% and a surface layer hardness of 700HV or more.

[0045] 3.Shot peening treatment Next, the shaft portion 12 of the test piece 10 was subjected to a shot peening treatment using an air type shot peening device equipped with an injection nozzle. The test piece 10 was placed at a distance of 200 mm from the injection nozzle, with the projection angle perpendicular to the machined surface of the shaft portion 12. The test piece 10 was then rotated on a rotating table at 30 rpm (= 1 rotation per 2 seconds), and the surface of the shaft portion 12 was subjected to a shot peening treatment. Here, the projection time was set so that the coverage was 300%.

[0046] For the examples in which "two stages" is written in the shot conditions column in Table 1, shot peening was performed in two stages. In the first shot peening, the shot material used had a particle size of φ0.3-1.0mm and a hardness of 700-1000HV, and the shot pressure (air pressure) was in the range of 0.3-0.6MPa. In the second shot peening, the shot material used had a particle size of φ0.05-0.2mm and a hardness of 700-1000HV, and the shot pressure (air pressure) was in the range of 0.3-0.6MPa.

[0047] On the other hand, for the examples in which "one stage" is written in the shot condition column in Table 1, shot peening was performed in only one stage. In this case, the blast material used had a particle size of φ0.3 to 1.0 mm and a hardness of 700 to 1000 HV, and the blast pressure (air pressure) was in the range of 0.3 to 0.6 MPa.

[0048] 4. Evaluation of test specimens The thus treated test piece 10 was evaluated for microstructure observation, equivalent hardness H, compressive residual stress, arithmetic surface roughness (Ra), static torsional strength, and torsional fatigue strength by the following methods.

[0049] 4-1.Tissue observation Using test piece 10 after vacuum carburization (before shot peening), edge portion 20 (see FIG. 1) of through hole 18 was cut out and edge portion 20 was confirmed. In detail, the observation surface was mirror-polished and then etched with nital, and the presence or absence of carbide in edge portion 20 was confirmed using an optical microscope (magnification 100 to 400 times). If carbide was found, it was judged as "excessive carburization present," and if carbide was not found, it was judged as "no excessive carburization present."

[0050] 4-2. Equivalent hardness H As shown in Fig. 2, in a cross section perpendicular to the axis in the shaft portion 12 of the test piece 10 after the shot peening treatment, hardness was measured from the outer surface 16 toward the inside along a virtual line m that passes through the center of the cross section and extends in the radial direction, using a micro Vickers hardness tester. In Fig. 2(B), the locations indicated by P1, P2, P3... are the positions of the hardness measurement points. The measurement intervals were 0.05 mm pitch from the outer surface 16 to a depth of 0.5 mm, 0.1 mm pitch from a depth of more than 0.5 mm to 1 mm, and 1 mm pitch at a depth of more than 1 mm. Here, the hardnesses measured at the hardness measurement points P1, P2, P3..., respectively, are designated as H1, H2, H3.... Next, the area in the cross section of the object to be measured is divided into small annular areas each including the hardness measurement points P1, P2, P3, etc., and the areas K1, K2, K3, etc. (mm 2 ) was correlated with the representative hardnesses H1, H2, H3... (HV) of the small regions, and the equivalent hardness H was calculated using the above formula (1).

[0051] 4-3.Compressive residual stress The compressive residual stress of the shaft portion 12 of the test piece 10 after shot peening was measured using the X-ray stress measurement method using X-ray diffraction, which is a common non-destructive method specified in "JIS B2711." Since the test piece 10 in this case has a martensitic structure, the measurement was performed using the type of characteristic X-rays = CrKα rays and the X-ray stress coefficient k = -318 [MPa / °].

[0052] 4-4.Surface roughness The arithmetic surface roughness Ra in the axial direction was measured for the outer surface 16 of the shaft portion 12 of the test piece 10 after the shot peening using a surface roughness measuring device (SURFCOM1500SD-13 manufactured by Tokyo Seimitsu Co., Ltd.). The measurement length was 8 mm, the cutoff wavelength was 0.8 mm, and the slope correction was a least-squares curve correction.

[0053] 4-5.Static torsional strength Using a torsion tester, the test piece 10 after shot peening was twisted at 5 deg / min, the torsion angle and torque until fracture were measured, and the torque at the proportional limit (proportional limit torque) was taken as the static torsional strength. The target static torsional strength was set at 1,300 N·m, which is approximately 1.23 or more compared to the proportional limit torque when conventional high-strength steel for gas carburizing (SCR420H) is subjected to gas carburizing and shot peening (single stage).

[0054] 4-6. Torsional fatigue strength Using a torsion tester, repeated torsional torque was applied to the test piece 10 after shot peening at a frequency of 0.5 to 3 Hz, and the number of cycles until torsional fracture was plotted. 4 fatigue strength and 10 5 The fatigue strength was calculated. The target for torsional fatigue strength is 10 5 In terms of fatigue strength, the 10-cycle fatigue strength was higher than that of conventional high-strength steel for gas carburizing (SCR420H) that had been subjected to gas carburizing and shot peening (single stage). 5 The fatigue strength ratio was set at 1100 N m or more, which is approximately 1.38 or more.

[0055] The evaluation results are shown in Table 2 below and FIG.

[0056] [Table 2]

[0057] The evaluation results in Table 2 reveal the following: Comparative Examples 1, 3, and 4, which were subjected to shot peening in only one step, had an arithmetic mean roughness (Ra) of more than 0.80 μm, and a compressive residual stress of less than 1200 MPa, which resulted in the target torsional fatigue strength not being achieved.

[0058] Comparative Example 2 is an example in which the Si content is less than the lower limit of the present invention. Excessive carburization was observed after vacuum carburization, and the torsional fatigue strength did not reach the target. Comparative Example 5 is an example in which the Cr content was excessively added, exceeding the upper limit of the present invention. In this case as well, excessive carburization was observed after vacuum carburization, and the target torsional fatigue strength was not achieved.

[0059] Comparative Example 6 is an example in which the C content is less than the lower limit of the present invention. In this Comparative Example 6, the equivalent hardness H did not reach the 490 HV specified in the present invention, and the static torsional strength (proportional limit torque) did not reach the target. As shown in Figure 3, a correlation is observed between the equivalent hardness H and the proportional limit torque, and it is clear that in order to achieve the target static torsional strength (1300 N m or more), an equivalent hardness H of 490 HV or more is necessary. As described above, in Comparative Examples 1 to 6, the targets were not achieved in either the static torsional strength or the torsional fatigue strength.

[0060] In contrast, in Examples 1 to 10, in which the chemical composition of the steel was within the range of the present invention and shot peening was performed in two stages, no excessive carburization occurred after vacuum carburization, and the arithmetic mean roughness (Ra), compressive residual stress, and equivalent hardness H were within the ranges specified by the present invention. As a result, the targets for both static torsional strength and torsional fatigue strength were achieved.

[0061] Although the present invention has been described in detail above, the present invention is not limited to the above-mentioned embodiments and examples, and various modifications are possible within the scope of the present invention.

Claims

1. By mass% 0.21<C<0.40 0.60<Si<2.00 0.20<Mn<2.00 P<0.020 S<0.020 0.09≦Cu<1.00 0.26≦Ni<2.00 0.20<Cr<0.75 0.31≦Mo<1.00 0.005<Al<0.100 0.010<Ti<0.100 0.010<Nb<0.100 0.0005<B<0.0030 N < 0.005 and the balance being Fe and unavoidable impurities, and the high-strength part has a carburized and hardened layer in a surface layer portion thereof, The arithmetic mean roughness (Ra) of the surface is 0.80 μm or less, and the compressive residual stress is 1200 to 1650 MPa. Furthermore, the high-strength part is characterized in that an equivalent hardness H defined by the following formula (1) based on the hardness distribution from the surface to the center of the inside is 490 HV or more. H = Σ(K i × H i ) / ΣK i ・・ Equation (1) However, Σ(K i ×H i ) is the area K of a small region partitioned in the cross section of the measurement object i (mm 2 ) and the representative hardness H i (HV) products for all small regions, ΣK i is the area of ​​all the small regions (mm 2 )

2. In claim 1, in mass % 0<V<0.30 A high-strength part further comprising:

3. A method for producing a high-strength part having a surface with an arithmetic mean roughness (Ra) of 0.80 μm or less, a compressive residual stress of 1200 to 1650 MPa, and an equivalent hardness H of 490 HV or more as defined by the following formula (1) based on a hardness distribution from the surface to an internal center, comprising the steps of: The steel according to claim 1 or 2 is processed into a part shape, and then vacuum carburized, quenched and tempered. Next, shot peening is performed using a projection material having a particle size of φ0.3 to 1.0 mm and a hardness of 700 HV or more, and then shot peening is performed again using a projection material having a particle size of φ0.05 to 0.2 mm and a hardness of 700 HV or more. H = Σ(K i × H i ) / ΣK i ··· Equation (1) However, Σ(K i ×H i ) is the area K of a small region partitioned in the cross section of the measurement object i (mm 2 ) and the representative hardness H i (HV) products for all small regions, ΣK i is the area of ​​all the small regions (mm 2 )

Citation Information

Patent Citations

  • Machine structural member and shaft obtained by using the same

    JP2006152330A

  • Pulley for belt type cvt

    JP2009185321A

  • Shot-peening method for forming gear excellent in abrasion resistance and pitching strength

    JP2014210294A

  • Carburized component excellent in wear resistance and fatigue characteristic, and process for producing the same

    JP2018053337A

  • Carburized component and manufacturing method therefor

    WO2010137607A1